2020
DOI: 10.1016/j.heliyon.2020.e03285
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Jatropha curcas seed oil content and fatty acid composition with fruit maturity stage

Abstract: Seed oil production in Jatropha seeds through different maturity stages have been investigated. In order to meet the high demand of oil (feedstock) for large scale biodiesel production, increasing oil content or output in Jatropha seeds is required. Jatropha fruits were harvested at four different maturity stages and the seeds were analysed for oil content. The seed oil was analysed for fatty acid profile. Results from four different geographical locations investigated namely; Mmadinare, Thamaga, Maun and Shas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 14 publications
(17 reference statements)
5
15
0
Order By: Relevance
“…The second dominant saturated fatty acid in rosehip seeds was found to be stearic acid ( Table 3 ), which agreed with the findings published by Barros et al [ 25 ]. Our results show that the stearic acid content in the samples ranged from 0.975% to 2.76%.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The second dominant saturated fatty acid in rosehip seeds was found to be stearic acid ( Table 3 ), which agreed with the findings published by Barros et al [ 25 ]. Our results show that the stearic acid content in the samples ranged from 0.975% to 2.76%.…”
Section: Resultssupporting
confidence: 92%
“…It has been documented that unsaturated (MUFAs + PUFAs) fatty acids are chemically unstable and easily oxidized [ 25 ], therefore, a high amount of these fatty acids in rosehip seed oil makes it susceptible to oxidation as well as degradation. In addition, it can be deduced that reduction of fat content in the seed samples during ripening stage V is the result of the breakdown of some unsaturated fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the quantities of all the unsaturated fatty acids showed a steady decrease with fruit maturity. This aligns with the submission of [37] that observed decrease in the unsaturated fatty acid content of Jatropha seed oil as fruit maturation advance and associated it to the chemical instability of unsaturated fatty acids (easily oxidized), therefore making the oil susceptible to oxidation and degradation. It was also observed that the difference in quantity of unsaturated fatty acids to saturated fatty acids was significantly higher in unripe fruit oil compared with the ripe one.…”
Section: Fatty Acid Profilesupporting
confidence: 87%
“…The ESA in Tung oil is synthesized by an FADX, a conjugase X also derived from FAD2 [ 79 ]. Although the major FAs in Jatropha oil are 18:1 and 18:2, there are 1–2% of ESAs in seed TAG [ 80 ], suggesting that Jatropha seeds have a weak conjugase activity. The possibility exists that Jatropha acyltransferases, including JcLPAT2, acylate ESA into TAG.…”
Section: Resultsmentioning
confidence: 99%